2016
DOI: 10.4238/gmr.15028069
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of dexmedetomidine on the respiratory burst of neutrophils

Abstract: ABSTRACT. The immunosuppressive effects of dexmedetomidine, a highly selective and widely used a 2 -adrenoceptor agonist for sedation, analgesia, and stress management, are investigated in vitro. In the present study, the respiratory burst of human neutrophils separated from venous blood was evaluated with dexmedetomidine treatment after Escherichia coli stimulation. The effects of five concentrations of dexmedetomidine (1, 5, 10, 50, 100 µg/mL) were evaluated by rhodamine in a flow cytometer. The nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, the effect of dexmedetomidine on neutrophils and lymphocytes remains controversial. One study found that dexmedetomidine suppressed the phagocytic activity of human neutrophils, which was associated with a respiratory burst coupled with NO production 19 . However, no influence of dexmedetomidine on human neutrophil or lymphocyte functions during short‐term incubation was found in vitro studies 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of dexmedetomidine on neutrophils and lymphocytes remains controversial. One study found that dexmedetomidine suppressed the phagocytic activity of human neutrophils, which was associated with a respiratory burst coupled with NO production 19 . However, no influence of dexmedetomidine on human neutrophil or lymphocyte functions during short‐term incubation was found in vitro studies 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…According to this, in vitro studies have shown that clinically relevant concentrations of dexmedetomidine do not affect chemotaxis, phagocytosis, or superoxide production by human neutrophils (44). However, decreased human neutrophil phagocytosis of E. Coli, associated with suppressed respiratory burst, nitric oxide (NO) production, and induced nitric oxide synthase (iNOS) activity induced by dexmedetomidine have been reported (45).…”
Section: Sedatives and Tranquilizersmentioning
confidence: 99%
“…For another, DEX could inhibit the maturation and function of DCs by interfering with the synthesis and secretion of IL-12 and IL-23, thereby negatively regulating human immune function ( Chen G. et al, 2016 ). In addition, DEX can inhibit the protein hydrolysis and migration of phagosomes in DCs, reduce the expression and migration of class II MHC molecule I-Ab and costimulatory molecule CD86 and inhibit the proliferation of cytotoxic T lymphocytes and the secretion of IFN-γ, thereby exerting an immunosuppressive effect ( Ueshima et al, 2013 ; Chen S. L. et al, 2016 ). However, the interesting phenomena have been found in an animal experiments, in which DEX at different concentrations may have the opposite effect on the secretion of inflammatory mediators by DCs.…”
Section: Dex's Regulatory Effect On Immune Cells and Inflammationmentioning
confidence: 99%